KISARAN INANG BAKTERIOFAG SEBAGAI AGEN PENGENDALI BAKTERI MULTIDRUG-RESISTANT (MDR): HOST RANGE BACTERIOPHAGES AS CONTROL AGENTS FOR MULTIDRUG-RESISTANT (MDR) BACTERIA - Gaffar, Affan (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2025)
Antibiotic resistance has become a serious challenge in healthcare and the food industry due to the rise of multidrug-resistant (MDR) pathogenic bacteria. One promising alternative is the use of bacteriophages as a therapeutic agent, given their high specificity and ability to infect and eliminate target bacteria without disrupting normal microbiota. This study aims to examine the host range of bacteriophages as a control agent for MDR bacteria through a systematic literature review approach. Data were collected from indexed scientific journals discussing bacteriophage-bacteria interactions, the characterization of monovalent and polyvalent phages, and the effectiveness of phage therapy. The review findings indicate that bacteriophage adsorption mechanisms depend on specific receptors on the bacterial cell wall. Their host range is categorized as narrow (monovalent) or broad (polyvalent), with polyvalent phages being preferred in therapy due to their ability to infect multiple MDR bacterial genera. This study highlights that an in-depth understanding of bacteriophage host range is crucial for developing effective and sustainable phage therapy. Beyond clinical applications, bacteriophages also hold potential for food safety and pathogen detection. Future research is needed to explore the optimization of phage combinations and genetic engineering to enhance their effectiveness in combating MDR infections.